Synthesis and characterisation of several amides /cHanisah Hassan - Hanisah Hassan, 1987-; Hasnah Mohd. Sirat, supervisor; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2009